Genome-Wide Identification and Expression, Protein–Protein Interaction and Evolutionary Analysis of the Seed Plant-Specific BIG GRAIN and BIG GRAIN LIKE Gene Family - Mishra, Bhuwaneshwar S.; Jamsheer K, Muhammed; Singh, Dhriti; Sharma, Manvi; Laxmi, Ashverya (Frontiers in Plant Science, 2017)
BIG GRAIN1 (BG1) is an auxin-regulated gene which functions in auxin pathway and positively regulates biomass, grain size and yield in rice. However, the evolutionary origin and divergence of these genes are still unknown. In this study, we found that BG genes are probably originated in seed plants. We also identified that seed plants evolved a class of BIG GRAIN LIKE (BGL) genes which share conserved middle and C-terminal motifs with BG. The BG genes were present in all monocot and eudicot species analyzed; however, the BGL genes were absent in few monocot lineages. Both BG and BGL were found to be serine-rich proteins; however, differences in expansion and rates of retention after WGD were observed. Promoters of BG and BGL genes were found to be enriched with auxin-responsive elements and the Arabidopsis thaliana BG and BGL genes were found to be auxin-regulated. The auxin-induced expression of AthBG2 was found to be dependent on the conserved ARF17/19 module. Protein-protein interaction analysis identified that AthBG2 interact with regulators of splicing, transcription and chromatin remodeling. Taken together, this study provides interesting insights about BG and BGL genes and incentivizes future work in this gene family which has the potential to be used for crop manipulation.